PENILAIAN KINERJA DENGAN PERSPEKTIF PELANGGAN PERSPEKTIF PEMBELAJARAN DAN PERTUMBUHAN BALANCED SCORECARD - Pujawati, Putri; Eriswanto, Elan (Balance : Jurnal Akuntansi dan Bisnis, 2021)
Balanced scorecard is a method of performance appraisal that combines external and internal parties. This study aims to analyze the performance assessment of Sagaranten Health Center with customer perspective and learning perspective and balanced scorecard growth. This research was conducted at the Sagaranten Health Center in 2018-2019. This type of research is a descriptive study with a quantitative approach. The variables used are customer perspective and learning and growth perspective. Retrieval of data by questionnaire and documentation. The results showed that based on the customer's perspective, it was considered good, where from the overall dimensions of the questionnaire distributed by patients, they felt very satisfied for the services provided. Based on the learning and growth perspective is considered good, using 4 dimensions of the questionnaire from the total shows good value, because from the results of the questionnaire felt very satisfied.